Impact of surgical approach on prevalence of positive peritoneal cytology and lymph-vascular invasion in patients with early-stage endometrial carcinoma: a National Cancer Database study. Issue 7 (14th April 2021) - Nasioudis, Dimitrios; Ko, Emily M; Cory, Lori; Latif, Nawar
Abstract : Objective: To investigate the prevalence of positive peritoneal cytology and lymph-vascular invasion by surgical approach among patients with early stage endometrioid endometrial carcinoma undergoing hysterectomy. Methods: The National Cancer Database was accessed and patients with FIGO stage I endometrioid endometrial carcinoma (with no history of another tumor diagnosed) who underwent simple hysterectomy (open or minimally invasive) between January 2010 and December 2015 and had available data on the presence of lymph-vascular invasion and/or status of peritoneal cytology were selected for further analysis. The impact of a surgical approach on the odds of lymph-vascular invasion and positive peritoneal cytology was calculated after controlling for tumor grade, size, and depth of myometrial invasion. Results: A total of 74 732 patients who met the inclusion criteria were identified. The rate of minimally invasive hysterectomy was 75.7%. Data on peritoneal cytology status and lymph-vascular invasion were available for 50 185 and 71 641 patients, respectively. A higher proportion of patients who had minimally invasive hysterectomy had positive peritoneal cytology (4.4% vs 2.3%, p<0.001), and presence of lymph-vascular invasion (10.4% vs 9.2%, p<0.001). After controlling for tumor size, tumor grade, and disease substage, the performance of minimally invasive surgery was associated with higher odds of positive peritoneal cytology (OR 2.08, 95% CI 1.83 to 2.37) and presence of lymph-vascular invasion (OR 1.33, 95% CI 1.25 to 1.41). After controlling for confounders there was no difference in survival between open and minimally invasive surgery groups (HR 0.93, 95% CI 0.85 to 1.004). Conclusions: Minimally invasive surgery may be associated with a higher incidence of positive peritoneal cytology and lymph-vascular invasion among patients with early stage endometrioid endometrial cancer. There was no difference in overall survival between patients who had laparotomy or minimally invasive surgery.